Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T19:23:57+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c)10=4-2x
2x=4-10
2x=-6/:2
x=-3
d)-(2x+1)=4
-2x-2=4
-2x=4+2
-2x=6/:(-2)
x=-3
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
-t=6+1
-t=7/:(-1)
t=-7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=-6+4
x=-2
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=-18+18
0=0 równanie tożsamościowe
i)(x-7)- 2(3x+5)=3
x-7-6x-10=3
-5x=3+17
-5x=20/:(-5)
x=-4
1 5 1
2010-02-10T19:25:02+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=10/-5x
x=2 (albo -2)

b)2x-2=7-x
2x+x=2+7
3x=9/3
x=3

Myślę ze dalej sobie poradzisz :)
2010-02-10T19:33:54+01:00
A) -3x=2x-10
-3x-2x=-10
-5x=-10/:(-5)
x=2
b) 2x-2=7-x
2x+x=7+2
3x=9/:3
x=3
c) 10=4-2x
2x=4-10
2x=-6/:2
x=-3
d) -(2x+1)=4
-2x-1=4
-2x=4+1
-2x=5/:(-2)
x=-5/2
x=-2 1/2 (2 cale i jedna druga)
e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f) 2t-(3t+1)=6
2t-3t-1=6
-t=7/*razy (-1)
t=-7
g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0
i) (x-7)- 2(3x+5)=3
x-7-6x-10=3
5x=20/:5
x=4